Food system under COVID-19 lockdown in Shanghai: problems and countermeasures - Han, Shuyu; Jia, Lei; Liu, Zengjin; Fuyuki, Katsuhito; Imoto, Tomoko; Zhao, Xintong (Frontiers in Sustainable Food Systems, 2024)
Introduction Owing to the increased transmissibility of the Omicron virus, Shanghai implemented a citywide lockdown in 2022. This measure disrupted the normal functioning of the city’s food system and led to incidents related to food insecurity within the city. To mitigate these challenges, the local government and various stakeholders devised various solutions. Methods In this context, we adopted a root cause analysis to report the disruptions caused by the lockdown on Shanghai’s food system. Results According to disruptions, we listed the challenges faced by Shanghai’ food system and solutions implemented by the government and stakeholders. Discussion We discussed the underlying reasons behind food system disruptions and listed advantages of Shanghai’s solutions. We further scrutinized the sustainability of the solutions implemented in Shanghai. Finally, we discussed how to promote the urban food system resilience building based on research findings. The findings of this research are anticipated to provide valuable insights for other areas that may encounter similar challenges in the future while fortify their urban food systems.